SOCIO-CULTURAL IMPACTS OF DEVELOPMENT CHANGES IN PEOPLE'S LIFESTYLE AND ENVIRONMENT - Wika Nurfuadi; Harahap, Isnaini (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Development is a complex process that has significant impacts on the social, cultural and environmental aspects of society. This research aims to explore the socio-cultural impacts of development, especially in the context of changes in people's lifestyle and their interaction with the environment. Through a qualitative approach and literature review, this research identifies various impacts generated by development, including changes in social interaction patterns, transformation of cultural values, as well as environmental damage. The findings show that infrastructure development and modernization often lead to the loss of local wisdom and traditional values, and increase individualism among communities. In addition, negative impacts on the environment, such as pollution and degradation of natural resources, also affect the way of life of people who depend on the ecosystem. This research also highlights the importance of integrating local wisdom as an adaptation strategy in sustainable development. The proposed policy recommendations include the integration of the Sustainable Development Goals (SDGs), increasing community participation in decision-making, and strengthening environmental protection policies. Thus, this research provides an important contribution in formulating more inclusive and sustainable policies to achieve a balance between economic progress and cultural and environmental preservation.